Promising results from a residential rehabilitation intervention focused on fatigue and the secondary psychological and physical consequences of cardiac arrest: The SCARF feasibility study. (April 2022) - Joshi, Vicky L.; Tang, Lars Hermann; Kim, Young Joo; Wagner, Mette Kirstine; Nielsen, Jørgen Feldbæk; Tjoernlund, Morten; Zwisler, Ann-Dorthe
Abstract: Aims: This study investigated the feasibility and potential effect of SCARF (Survivors of Cardiac ARest focused on Fatigue) a multidisciplinary residential rehabilitation intervention focused on fatigue and the secondary psychological and physical consequences of cardiac arrest (CA). Methods: This was a prospective one-armed feasibility study. Six progression criteria were identified related to the feasibility of the intervention and viability of a future effect study in terms of: participant recruitment (1), participant retention (2, 3, 4), and completeness of outcomes (5, 6). Data on participant/clinician satisfaction with the intervention was also collected along with self-reported outcomes: fatigue, quality of life, anxiety, depression, function and disability, and physical activity (at baseline, 12 weeks and 6 months) and physical capacity (baseline and 12 weeks). Results: Four progression criteria were met including retention (87.5%) and completion of baseline outcomes (97.5%). Two criteria were not met: recruitment rate was 2.9 participants per month (estimated rate needed 6.1) and completion of final outcomes was 65% (estimated proportion needed 75%). Participant/clinician satisfaction with the intervention was high. Three months after the SCARF intervention small to moderate effect size changes of r = 0.18–0.46 were found for self-reported fatigue, quality of life, anxiety, depression, function and disability and for two of the physical capacity tests ( d = 0.46–0.52). Conclusion: SCARF was found to be a feasible intervention with high participant/clinician satisfaction, high participant retention and the possible potential to improve self-reported and physical capacity outcomes. Procedures for study recruitment and collection of final outcomes should be modified before a fully powered randomised controlled trial is conducted.